2020
DOI: 10.1371/journal.pone.0241493
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane mosaic virus mediated changes in cytosine methylation pattern and differentially transcribed fragments in resistance-contrasting sugarcane genotypes

Abstract: Sugarcane mosaic virus (SCMV) is the causal agent of sugarcane mosaic disease (SMD) in Brazil; it is mainly controlled by using resistant cultivars. Studies on the changes in sugarcane transcriptome provided the first insights about the molecular basis underlying the genetic resistance to SMD; nonetheless, epigenetic modifications such as cytosine methylation is also informative, considering its roles in gene expression regulation. In our previous study, differentially transcribed fragments (DTFs) were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 96 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Previous studies showed that the infection of potyviruses, e.g., TuMV and SCMV caused comprehensive changes of DNA methylation in host plant (da Silva et al 2020;Corrêa et al 2020). In this study, we further analyzed the methylome change in virus-infected cells to insight the arms race between virus and host at the DNA methylation level.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that the infection of potyviruses, e.g., TuMV and SCMV caused comprehensive changes of DNA methylation in host plant (da Silva et al 2020;Corrêa et al 2020). In this study, we further analyzed the methylome change in virus-infected cells to insight the arms race between virus and host at the DNA methylation level.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a heavy metal-associated isoprenylated plant protein was shown to interact with the Pomovirus movement protein, affecting virus long-distance movement (Cowan et al ., 2018). Interestingly, transcripts of two chaperones and a heavy metal-associated isoprenylated protein differentially accumulated in response to SCMV in sugarcane (da Silva et al, 2020). Another protein annotated in the present study that has been shown to interact with the potyviral movement protein P3N-PIPO is a beta-glucosidase, possibly facilitating viral spread through the plant (Song et al ., 2016); beta-glucosidase genes have also been found in QTLs for resistance to SCMV and other potyviruses (Gustafson et al ., 2018; Rubio et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of our analysis, biological processes enriched in SCMV resistance-associated modules included stress responses, regulation of transcription and translation, and a process that has long been known to be affected by SCMV infection (Irvine, 1971) but has not been featured by the analysis of genes directly associated with resistance— photosynthesis. Recent transcriptomic and proteomic studies have shown that infection by SCMV indeed affects the regulation of genes and proteins involved in these processes (Wu et al ., 2013; Chen et al ., 2017; Akbar et al ., 2020; da Silva et al ., 2020). Notably, the results of our coexpression network analyses indicate that the expression of genes identified in the present study as being associated with SCMV resistance are also associated with those controlling such processes; thus, those genes possibly play roles in their regulation during viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation